1 December, 01:26

# Find a polynomial equation that has zeros at x = 0, x = - 5 and x = 6

+1
1. 1 December, 01:32
0

Step-by-step explanation:

Data

x = 0; x = - 5; x = 6

Process

1. - Equal the zeros to zero

x₁ = 0; x₂ + 5 = 0; x₃ + 6 = 0

2. - Multiply the results

x (x + 5) (x + 6) = x [ x² + 6x + 5x + 30]

3. - Simplify

= x [ x² + 11x + 30]

4. - Result

= x³ + 11² + 30x
2. 1 December, 01:46
0
x³ - x² - 30x = 0

Step-by-step explanation:

Given that a polynomial has zeros at x = 0, x = - 5 and x = 6.

We convert these into factors by rearrange each equation above to convert the equation into the following form:

{expression} = 0

for x = 0 (x = 0 is the 1st factor. already in correct form, no further manipulation needed)

for x = - 5 (add 5 to both sides)

x + 5 = 0 (x + 5 is the 2nd factor)

for x = 6 (subtract 6 from both sides)

x - 6 = 0 (x - 6 is the 3rd factor)

to obtain the polynomial equation, simply multiply all the factors together and equate to zero, i. e.

(x) · (x+5) · (x-6) = 0

expanding this, we will get

x³ - x² - 30x = 0